How animals see the world comparative behavior, biology, and evolution of vision - Lazareva, Olga F.; Shimizu, Toru.; Wasserman, Edward A. (New York ; Oxford : Oxford University Press, 2012)
The visual world of animals is highly diverse and often very different from that of humans. This book provides an extensive review of the latest behavioural and neurobiological research on animal vision, detailing fascinating species similarities and differences in visual processing.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Mar. 5, 2012).
Keywords: Vision; Animal behavior; Evolution (Biology); Eye -- Evolution; Physiology, Comparative